Entry regulations, product differentiation and determinants of market structure - Florin Maican; Matilda Orth (Research Institute of Industrial Economics (IFN), 2013)
We use a dynamic oligopoly model of entry and exit to evaluate how entry regulations affect profitability and market structure in retail. The model incorporates demand and store-level heterogeneity. Based on unique data for all retail food stores in Sweden, we find that the average entry costs for small and large stores are 10 and 18 percent lower, respectively, in markets with liberal compared with restrictive regulations. Counterfactual simulations show that lower entry costs in restrictive markets result in higher entry rates and allow us to quantify the consequences of regulations in light of trade-offs between small and large stores.
Keywords: L11; L13; L81; 330; Imperfect competition; product differentiation; retail markets; entry; exit; sunk costs